2015
DOI: 10.1111/1475-6773.12283
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Disease Management and Risk of Mortality in English Primary Care Practices

Abstract: Objective. To investigate whether better management of chronic conditions by family practices reduces mortality risk. Data. Two random samples of 5 million patients registered with over 8,000 English family practices followed up for 4 years (2004/5-2007/8). Measures of the quality of disease management for 10 conditions were constructed for each family practice for each year. The outcome measure was an indicator taking the value 1 if the patient died during a specified year, 0 otherwise. Study Design. Cross-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
7
0
1
Order By: Relevance
“…However, our findings suggest that people with SMI generally have the opportunity to be in receipt of the checks required by QOF, given the observed face-to-face consultation rates, although the effectiveness of these checks in improving patient health is still being debated. 40–43 In line with the national well-being and recovery agenda, consultation rates may continue to increase further as Community Mental Health Teams are encouraged to discharge all but the most severe cases back to primary care. Conversely, the removal of cardiometabolic QOF indicators (requiring annual recording of weight, blood cholesterol and glucose) in 2014 might curb such an increase.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings suggest that people with SMI generally have the opportunity to be in receipt of the checks required by QOF, given the observed face-to-face consultation rates, although the effectiveness of these checks in improving patient health is still being debated. 40–43 In line with the national well-being and recovery agenda, consultation rates may continue to increase further as Community Mental Health Teams are encouraged to discharge all but the most severe cases back to primary care. Conversely, the removal of cardiometabolic QOF indicators (requiring annual recording of weight, blood cholesterol and glucose) in 2014 might curb such an increase.…”
Section: Discussionmentioning
confidence: 99%
“…An electronic booking system (Choose and Book) was introduced in 2005/6 to allow direct booking of referrals from general practices. By 2012/13, 50% of all referrals were made via the system ( Dusheiko and Gravelle, 2015 ). Since 2007 the NHS Choices website has provided public information on the location, services and quality of providers.…”
Section: Introductionmentioning
confidence: 99%
“…12 International studies have demonstrated that improving the process quality of primary care is associated with reduced emergency admissions, improved patient outcomes and reduced costs to the health-care system. [78][79][80] Moreover, small improvements in primary care process quality can have significant effects on population health at low cost. 81 Improving the quality of primary care has been incentivised in several countries, primarily using financial incentives.…”
Section: Primary Care Qualitymentioning
confidence: 99%
“…Furthermore, there is uncertainty about how long it takes for improvements in health-care delivery to feed through into reductions in preventable hospitalisation and amenable mortality. It is reasonable to expect some short-term impact within a year or two, 80 although the length of lag is likely to vary by disease and type of intervention; for example, reductions in mortality because of improved management of heart disease and diabetes may be more rapid than reductions as a result of earlier diagnosis and referral for suspected cancer.…”
Section: Implications For Clinicians Policy-makers and Managersmentioning
confidence: 99%